Mathematical Modeling of Suspension Filtration on a Rapid Filter at an Unregulated Rate (MCIT: Proceedings of International scientific and practical conference, 2021)
Mathematical modeling of detachable filtration in the split filter flow mode was carried out using exact and approximate analytical methods. An engineering technique has been developed to determine the duration of filter cycles, based on quality, economic and technical criteria. Determination of rational filter medium height was considered for two materials differed significantly by economic indexes.
Keywords: filtration, modeling, suspension, exact solution, height, split filter flow